Legal Protection for The Misuse of Indosiar Logo on Video Content of Mobile Service Parody on Instagram Application - Dhea Titania Octavia Putri; R Rizka (Proceeding International Conference Restructuring and Transforming Law, 2024)
The utilization of internet technology has significantly impacted various aspects of human life, especially in the realm of social media. Instagram, as one of the main social media platforms, provides a space for individuals to share various types of multimedia content, including parody content. However, in this context, issues of intellectual property rights, particularly concerning the misuse of company logos, have become increasingly relevant. The objective of this article is to examine the legal safeguards concerning the improper utilization of the Indosiar logo within parody materials found on Instagram. Using a normative legal approach and case study methodology, this research identifies legal violations occurring under the Copyright Law and Trademark Law. Additionally, it highlights Instagram's policies as an electronic system provider in addressing logo misuse. The results of this study reveal that the inappropriate use of corporate logos in Instagram parody content raises a conflict between the freedom of expression and intellectual property rights. Although parody content aims to entertain, unauthorized logo usage constitutes a trademark infringement that can damage a company's reputation. Hence, ensuring legal safeguards for intellectual property rights in the digital era necessitates collaboration among regulators, corporations, and social media platforms to establish a balanced framework benefiting all stakeholders.